"Go Girls!": psychological and behavioral outcomes associated with a group-based healthy lifestyle program for adolescent girls. Issue 1 (19th September 2014) - Dowd, A Justine; Chen, Michelle Y; Jung, Mary E; Beauchamp, Mark R
Abstract: The objective of this study was to assess changes in adolescent girls' health-enhancing cognitions and behaviors targeted by the Go Girls! group-based mentorship lifestyle program. Three hundred and ten adolescent girls (nested within 40 Go Girls! groups) completed questionnaires that assessed cognitions (attitudes, self-regulatory efficacy, and intentions) and behaviors (physical activity and dietary) at four time points (two pre-program, one at the end of the program, and one at 7-week follow-up). Hierarchical linear modeling was used to examine changes in the outcome variables among Go Girls! participants ( M age = 11.68 years, SD = 0.80). No significant changes occurred in the outcome variables during the baseline comparison period (Time 1–2). When compared to the average of the baseline assessments, 7 weeks after completing the program, girls reported significant improvements in physical activity ( M Baseline PAtotal = 3.82, SD = 3.49; M T4 PAtotal = 4.38, SD = 3.75) and healthy eating ( M Baseline = 10.71, SD = 1.13; M T4 = 11.35, SD = 1.05) behavior and related cognitions ( d values ≥0.65). Findings provide preliminary support for programs that foster belongingness and target health behaviors through mentorship models.